False Fruits of Knowledge A Rebuttal to Hirsch on Composition and Pedagogy - Blau, Sheridan ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1978)
E. D. Hirsch's call for authoritative knowledge about composition is flawed, according to this document, because he focuses on the product and not the process of composing, thereby excluding more of the problem of composition than he includes. Hirsch's principle of readability--that styles that communicate meaning with less effort from the reader are better--provides him with a rationale for guiding research and instruction and with the basis for objective standards for evaluators themselves. Readability may be important, but not as important as Hirsch thinks. He puts too much emphasis on revising and editing meaning that is "already there," and on seeing all student problems as ignorance that can be cured by the acquisition of knowledge about readability. In fact, Hirsch's kind of instruction in readability itself seems to be the source of many student writing problems. Since most students can already write readable prose in some situations, the task of English instruction is to help students extend their capacity to write for new purposes. Composition is probably closer to dialogue than to Hirsch's model of forensic speech, and Hirsch's emphasis on rules, maxims, and readability reveals what is missing at the center of his philosophy--students and their learning needs. The complexity of the language process and the often tacit nature of learning reveal that teachers should create contexts that give students the best chance to acquire skills, not lay down rules. (JL)
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Educational Principles; Elementary Secondary Education; Higher Education; Learning Processes; Linguistic Theory; Readability; Revision (Written Composition); Student Needs; Writing (Composition); Writing Evaluation; Writing Instruction; Writing Processes; Hirsch (E D); Opinion Papers; Guides, Classroom -- Teacher